Sustainable cross-border partnerships as academic diplomacy: A reflexive Europe–Africa case study - Anne, Djiby; Clausen, Lisbeth (Journal of Interdisciplinary Studies in Education, 2026)
In the context of geopolitical tensions and accelerated digital transformation, cross-border partnerships increasingly play a key role in sustaining academic diplomacy through knowledge cocreation. While internationalization has traditionally focused on student mobility, limited attention has been given to individual initiatives and how these can evolve into sustainable research collaborations supported by hybrid mobility and digital mechanisms. This paper examines how an encounter during an International Teacher’s Program in 2022 in France led to multi-country collaboration and co-writing linking Denmark, Senegal, and Morocco. Drawing on a 2-year qualitative case study based on collaborative documentation, fieldwork in Senegal, reflective interviews among partners, and digital interaction archives, the study employs an inductive thematic analysis to identify enabling mechanisms of sustained cross-border cooperation. The results reveal four interrelated dimensions of sustainable academic diplomacy enabling collaboration across geographic and institutional transitions: (1) relational capital built through immersive mobility, (2) embedded mobility combining physical and contextual presence, (3) knowledge co-production grounded in local perspectives, and (4) digital continuity. This study proposes an evidence-based framework for global partnerships.